Die Verbreitung der Vegetation im Kaghan-Tal (Westhimalaya, Pakistan) und ihre kartographische Darstellung im Maßstab 1: 150 000 - Schickhoff, Udo (ERDKUNDE, 1994)
Since the vegetation map of the Himalayas by SCHWEINFURTH was published in 1957 there has been hardly any progress regarding the cartographic representation of the vegetation patterns, especially in the Western Himalayas. In this region the vegetation map of Kaghan is only the second map on a larger scale after the vegetation map of Nanga Parbat by TROLL, which was already published in 1939. The Kaghan map was surveyed within the framework of geoecological studies emphasizing vegetation ecology. The vegetation units were differentiated on the basis of a floristic-sociological typification of the plant communities, which was carried out according to the Braun-Blanquet approach for the first time on the southern declivity of the West Himalayan Range. Some flanks and side valleys, which could not be inspected due to the vastness of the area, were left as white patches. The Kaghan Valley is marked by a distinct three-dimensional change of climate, soils and vegetation. The climate is the main factor for the differentiation of the natural vegetation. It shows a transitional character encompassing two different precipitation regimes. In the humid Lower Kaghan the influence of the tropical summer monsoon is predominant. Pinus roxburghii- and Acacia-Olea-forests, adapted to the monsoon regime, form the natural vegetation cover in the lower montane belt, giving way to mediterranoid Quercus baloot- and Cedrus deodara-forests above Paras. In the rain shadow of the outer mountain chains the monsoonal rains are enormously decreasing towards the upper valley whereas the winter/spring precipitation is steadily increasing. Moist-temperate coniferous forests (Abies pindrow-, Pinus wallichiana-, Cedrus deodara-forests) are prevailing on all aspects above Mahandri. They are covering as well the upper montane and subalpine belt in the lower and middle section of the valley. In the upper subalpine belt Betula utilis-forests are forming the upper treeline turning into Salix-krummholz. On south-facing slopes they are replaced by Pinus wallichiana-stands and Juniperus squamata-heaths. The vegetation cover of the alpine belt consists mainly of Cyperaceae-mats (different Kobresia-communities) and dwarf scrub heaths of Juniperus squamata (sunny slopes) and Rhododendron anthopogon (shady slopes). In Upper Kaghan (Battakundi Area), where an average two-monthly arid period occurs, the sunny slopes are covered by xeric Artemisia maritima-steppes interspersed with tree clumps of Juni Perus macropoda. In the course of evolution of the cultural landscape half of the potential forest areas have been converted to farm- and rangeland. It is due to the Forest Department, established in 1864, that large forest areas are being protected from further degradation and depletion.